Experimental animal models for polycystic ovarian syndrome (methods, effects, and implications) - Erna Yovi Kurniawati; Noor Pramono; Syarief Thaufik Hidayat; Endang Mahati (Livestock and Animal Research, 2024)
Many studies have replicated the clinical and genetic features of polycystic ovarian syndrome (PCOS) using a range of experimental animal models to improve treatment outcomes. This article aims to present an overview of the various experimental animal models that have been used in PCOS research. In this study, we conducted a systematic review of relevant research articles on the induced animal model PCOS. We searched research articles in Indonesian and English published over the last five years through three databases: PubMed, ScienceDirect, Google Scholar. We use established inclusion and exclusion criteria to select suitable articles. Out of 19 research articles included in our systematic review, we found the animal model PCOS based Rotterdam criteria, PCOS-IR model, PCOS-Inflammation model, PCOS-Gut microbiota model and PCOS-syndrome metabolic model. Androgen agents such as testosterone propionate, free testosterone, DHEA, and letrozole, as well as sodium valproate, are effective in the induction of PCOS phenotypes based on the Rotterdam criteria (oligo/amenorrhea, hyperandrogenic, and polycystic ovaries).